2017
DOI: 10.1111/trf.14453
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of severe red blood cell alloimmunization in pregnancy with a combination of therapeutic plasma exchange, intravenous immune globulin, and intrauterine transfusion

Abstract: A combined regimen of TPE and IVIG early in pregnancy and IUT later in pregnancy results in successful management of severe maternal RBC alloimmunization and HDFN. IUT with fully phenotypically matched RBC units may help prevent further RBC alloimmunization in complex cases of HDFN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…This research included exclusively pregnancies complicated by anti-D and anti-Kell alloimmunization. Therapeutic plasma exchange, alone or in combination with immunoglobulin, to prevent or alleviate alloantibodies or to postpone the first IUT has been reported as an option in such pregnancies [24].…”
Section: Discussionmentioning
confidence: 99%
“…This research included exclusively pregnancies complicated by anti-D and anti-Kell alloimmunization. Therapeutic plasma exchange, alone or in combination with immunoglobulin, to prevent or alleviate alloantibodies or to postpone the first IUT has been reported as an option in such pregnancies [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several case series and case reports indicate a beneficial role of IVIG, at least in delaying the development of significant anemia [36]. Admittedly, focusing on the reported cases in the literature, the administration of IVIG varied considerably and was inadequate due to low doses, delayed administration (after fetal anemia was already present), and/or inconsequent administration in a number of cases (table 2) [30,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. Only one study has shown that the administration of 1 g/kg/week in four women with anti-D did not appear to improve outcomes of affected fetuses [58].…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancies over 35 weeks of gestation delivery is considered to be safer than IUT. The last IUT is advised to be performed at 30-32 weeks of gestation with subsequent delivery at 32-34 weeks of gestation, after steroid administration for fetal pulmonary maturation [19,20,21,22].…”
Section: Antenatal Diagnosis and Managementmentioning
confidence: 99%